The Direct Thrombin Inhibitors Dabigatran and Lepirudin Inhibit GPIbα-Mediated Platelet Aggregation - Trabold, Katharina; Makhoul, Stephanie; Gambaryan, Stepan; van Ryn, Joanne; Walter, Ulrich; Jurk, Kerstin (Thrombosis and Haemostasis, 2019)
The direct thrombin inhibitor (DTI) dabigatran is a non-vitamin K antagonist oral anticoagulant for the prevention of stroke and systemic embolism in patients with non-valvular atrial fibrillation. In addition to its anti-thrombotic efficacy, dabigatran has been suggested to exert some pro-thrombotic effect due to fostering the ligation of thrombin to its high affinity platelet receptor glycoprotein (GP) Ibα in patients with atrial fibrillation. On the other hand, we provided evidence that a member of another class of DTIs, lepirudin, stimulates the inhibitory cyclic guanosine monophosphate (cGMP)/soluble guanylate cyclase pathway in human platelets. Here, we investigated the effect of lepirudin and dabigatran spiked to platelets from healthy volunteers on GPIbα-mediated platelet aggregation and agglutination. Ristocetin/von Willebrand factor (vWF)-induced aggregation of platelets in the presence or absence of plasma was significantly inhibited by lepirudin, dabigatran and D-phenylalanyl-L-prolyl-L-arginine chloromethyl ketone (PPACK). However, ristocetin/vWF-mediated platelet agglutination and binding of vWF to platelets were not affected by the DTIs. The anti-aggregatory effect was confirmed by using the GPIbα-specific agonist echicetin beads for human and murine platelets. DTIs diminished echicetin beads-induced Syk Y352 phosphorylation (used here as readout for an early signal occurring during echicetin-induced platelet aggregation), but did not inhibit adenosine diphosphate- or thromboxane A2-induced platelet aggregation. Thrombin was not generated in response to ristocetin/vWF or echicetin beads and therefore did not explain the inhibitory effect of the DTIs. Therapeutic concentration of lepirudin and dabigatran did not affect significantly platelet vasodilator-stimulated phosphoprotein S239 phosphorylation or cGMP and cyclic adenosine monophosphate levels. These data suggest that the DTIs, lepirudin and dabigatran, impair platelet activation measured during platelet aggregation induced by ristocetin/vWF or echicetin beads.
Keywords: platelets; aggregation; direct thrombin inhibitors; von Willebrand factor; GPIb/V/IX